2005
DOI: 10.1029/2005gl024430
|View full text |Cite
|
Sign up to set email alerts
|

Observation of an abrupt disruption of the long‐term warming trend at the Balearic Sea, western Mediterranean Sea, in summer 2005

Abstract: The properties of the Western Mediterranean Deep Water in a wide area located at the western boundary of the Mediterranean Sea, including the Balearic Sea, have revealed intense changes when observed in summer 2005. Between February and June 2005, a temperature drop of 0.14°C reverted dramatically the progressive warming trend of 0.011°C yr−1 that had been observed since 1996, in the waters below 600 dbar north of the Balearic channels. A similar temperature drop has been observed east of the Minorca Island, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
101
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(121 citation statements)
references
References 24 publications
14
101
1
2
Order By: Relevance
“…The system of deep convection in the Gulf of Lions had a particularly intense event observed during winter of 2005 (López-Jurado et al, 2005;Canals et al, 2006;Schroeder et al, 2008) and to a lesser extent during the following years, when the convection occurred over a much larger and deeper area than usual. This intense formation of dense water in the Gulf of Lions has already been simulated by (Beuvier et al, 2012a(Beuvier et al, ) et al (2012a with the model used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system of deep convection in the Gulf of Lions had a particularly intense event observed during winter of 2005 (López-Jurado et al, 2005;Canals et al, 2006;Schroeder et al, 2008) and to a lesser extent during the following years, when the convection occurred over a much larger and deeper area than usual. This intense formation of dense water in the Gulf of Lions has already been simulated by (Beuvier et al, 2012a(Beuvier et al, ) et al (2012a with the model used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Winter 2005 was one of the coldest and driest winters in the last 40 years; the strong surface cooling and evaporation with highly favourable preconditioning triggered deep convection. López-Jurado et al (2005) suggested that the unusual characteristics of the 2005 convection event could be due to a change in the characteristics of the water masses advected until forming the zone of WMDWs after EMT. Herrmann et al (2010) rather suggest that the higher temperature and salinity of the new WMDW formed in 2005 are due to the absence of an intense convective winter in the 1990s and early 2000s in the NWMed, leading to an accumulation of heat and salt in the intermediate and deep layers of this area.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, during the ''deep phase'' the EMT induced the increase of the deep heat and salt contents. Successively the inflow of saltier and warmer water from the EMED at intermediate levels may have induced the formation of warmer and saltier deep water in the northwestern Mediterranean, as the intermediate water plays a key role in the convective processes in this area [Wu and Haines, 1996] [López-Jurado et al, 2005], the highly saline and warm characteristics can be attributed to the progressive salt and heat accumulation in the north-western Mediterranean during the previous years.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, most of this material remained in suspension and was transported within the along shore current to distal areas. In fact, cascading waters have been detected offshore as anomalies in water mass properties (Bethoux et al, 2002;Lopez-Jurado et al, 2005;Font et al, 2007). Palanques et al (2009) Lower slope station (SOS1900) recorded higher mass flux values than canyon mouth station (CCC1900).…”
Section: Impact Of Dswc On the Open Slopementioning
confidence: 99%